The Importance Of Adversity Quotient And Spiritual Quotient Capabilities For Consistent Performance Of Educators - Mayangsari, Mayangsari (Perhimpunan Sarjana Ekonomi dan Bisnis, 2021)
The magnitude of the teacher's responsibility is the basis for the importance of maintaining performance. Its role has a great contribution to all stakeholders, both the school and the students themselves. Therefore, several factors need to be considered, so that teacher performance is maintained, including improving problem-solving abilities and spiritual intelligence. This research was conducted to see how it is possible to maintain performance through strengthening the adversity quotient and spiritual quotient abilities. In order for this research to answer the problems and research objectives, a scientific method is established, namely a quantitative approach. The sources of data in this study were the teachers of Al-Madinah Islamic School, as many as 120 people, and the data were obtained through the distribution of questionnaires. The analysis method uses statistical regression techniques with the help of SPSS applications. The results of the study explain that the adversity quotient and spiritual quotient are proven to be able to maintain and improve teacher performance, with a contribution value of 0.404. This finding confirms the fact that the teaching profession requires complete abilities, ranging from personality, intellectual, emotional, to spiritual to be a factor in maintaining performance, so that quality education can be realized.